2019
DOI: 10.21307/jofnem-2019-085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a conservation agriculture system on soil characteristics, rice yield, and root-parasitic nematodes in a Cambodian lowland rice field

Abstract: Rice production in Southeast Asia is significantly affected by root-parasitic nematodes (RPN). The Green Revolution has encouraged new agricultural practices (e.g. intensive monoculture, high yielding rice variety) to respond to the high rice demand; however, these methods have promoted the spread of these pests. The recent banning of chemical nematicides resulted in a need for alternative sustainable control strategies. In the present study, we assessed the effects of a direct-seeding mulch-based cropping sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The age of rice and soil pH might influence nematode abundance, where greater numbers of nematodes extracted from rice stubbles were observed at soil pH 5.9 -6.0 than soil pH 5.3 -5.4. These results were similar to those reports by [11,18,20] who examined Hirschmanniella populations in paddy rice fields of Takeo, Battambang and Kampong Thom provinces, Cambodia. In addition, as Hirschmanniella are migratory endoparasites by nature, they are more prevalent in rice roots than in soil [21].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The age of rice and soil pH might influence nematode abundance, where greater numbers of nematodes extracted from rice stubbles were observed at soil pH 5.9 -6.0 than soil pH 5.3 -5.4. These results were similar to those reports by [11,18,20] who examined Hirschmanniella populations in paddy rice fields of Takeo, Battambang and Kampong Thom provinces, Cambodia. In addition, as Hirschmanniella are migratory endoparasites by nature, they are more prevalent in rice roots than in soil [21].…”
Section: Resultssupporting
confidence: 92%
“…The PCR was conducted by using extracted nematode DNA as the template. 30 µL of PCR reaction included 3 µL of DNA template, 9 µL of sterilized distilled water, 1.5 µL of each 10 µM forward and reverse primers {D2A (5′ ACAAGTACCGTGAGGGAAAGT 3′) and D3B (5′ TGCGAAGGAACCAGCTACTA 3′) [17] and rDNA2 (5'-TTGATTACGTCCCTGCCCTTT-3') and rDNA1.58s (5'-ACGAGCCCGAGTGATCCACCG-3') [18]}, and 15 µL of 2x PCR master mix with dye solution i-taq (Intron biotechnology, Korea). The PCR condition was programmed as follows: denaturation at 94 °C for 5 min, followed by 35 cycles of 94 °C for 30 s, 56 °C for 30 s and 72 °C for 1 min, and final extension at 72 °C for 5 min.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Puddling could significantly reduce nematodes in PTR, while nematodes such as RKN, Meloidogyne triticoryzae, and Tylenchorhynchus mashoodi were higher in DSR (Gaur and Singh, 1993;Chandel et al, 2002). Similarly, Suong et al (2019) found higher root-parasitic nematodes in rice under direct-seeded mulch-based cropping system than in conventional plow-based tillage in Cambodia. The populations of Tylenchorhynchus brevilineatus and Pratylenchus spp were significantly higher in ZT than in CT fields (Pankaj et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Cambodian soils are seriously threatened by inappropriate agricultural systems. The returns on taking actions against land degradation are estimated at 3 US dollars for every dollar invested in restoring cropping systems on soil health, and SOC sequestration have been reported in several studies (Hok et al, 2015(Hok et al, , 2018(Hok et al, , 2021Pheap et al, 2019;Suong et al, 2019;Sar, 2021;Koun et al, 2023), however, the information on the impact of long-term NT systems on the changes in SOC stock remains scarce in the country as well as in Southeast Asia. There is a need to document the long-term changes in SOC stocks under CA and NT cropping systems to fill in the knowledge gaps as well as provide robust evidences to land use planners and policymakers.…”
Section: Introductionmentioning
confidence: 99%